The Burden of Movement Disorders in Cameroon: A Rural and Urban‐Based Inpatient/Outpatient Study. Issue 4 (11th March 2017) - Cubo, Esther; Doumbe, Jacques; Mapoure Njankouo, Yacouba; Nyinyikua, Theophile; Kuate, Callixte; Ouyang, Bichun; Shah, Hiral; Calvo, Sara; Fernandez‐Sierra, Abel; Kompoliti, Katie; Njiengwe, Erero; Louis, Elan D.
Abstract: Background: Because of rapid demographic changes, the prevalence of movement disorders (MDs) is expected to increase in Africa. The objective of this study was to estimate the prevalence of MDs in an inpatient/outpatient‐based study of rural and urban health care centers in Cameroon. Methods: In this retrospective medical chart review, the inpatient/outpatients settings covered an urban population (3, 000, 000) and a rural population (380, 276). Neurological diseases were classified according to the International Statistical Classification of Diseases‐Related Health Problems, 10th revision (ICD‐10). Crude prevalence was calculated per 100 with 95% confidence intervals (CIs). Results: Of 20, 131 medical charts reviewed (13% from the rural area), 4187 patients (20.8%) with neurological complaints were identified. MDs were diagnosed exclusively from urban centers in 134 patients (3.2%): the mean patient age was 48.6 ± 18.6 years, and 54.7% were women. The most prevalent MDs were hyperkinetic movements (tremor, myoclonus, and drug‐induced MDs [ICD‐10 code G25]; prevalence, 1.19%; 95% CI, 1.192–1.194%), Parkinson's disease (ICD‐10 code G20; prevalence, 0.78%; 95% CI, 0.785–0.787%), dystonia (ICD‐10 code G24; prevalence, 0.61%; 95% CI, 0.612–0.613%), secondary parkinsonism (ICD‐10 code G21; prevalence, 0.56%; 95% CI, 0.564–0.565%), Huntington's disease (ICD‐10 code G10; prevalence, 0.09%; 95% CI, 0.091–0.092%), and ataxia (ICD‐10 code R29; prevalence, 0.04%; 95% CI, 0.0451–0.0456). Conclusion: Although the burden of MDs is expected to increase, MDs are likely underdiagnosed in rural areas. High‐quality movement disorder training is essential to tackle this need.